Greater in vivo than in vitro pulsatility of insulin secretion with synchronized insulin and somatostatin secretory pulses. - Matthews, DR; Hermansen, K; Connolly, A; Gray, D; Schmitz, O; Clark, A; Orskov, H; Turner, R (1987)
To examine the control of pulsatile insulin secretion by an intrapancreatic pacemaker, samples at minute intervals were taken from the portal vein in dogs in vivo and from an isolated perfused pancreas preparation in vitro. Anesthetized dogs had high amplitude pulsatile insulin secretion which was not consistently regular. Fourier transform analysis showed dominant 20- and 10-min periods of spectral power (P less than 0.01). After vagotomy, the relative oscillatory power was reduced from 83% to 42%, about a lower mean concentration with abolition of the 20-min oscillations. The isolated perfused dog pancreas also had oscillatory insulin secretion with oscillatory power of 12%. Autocorrelation showed regularity of in vitro insulin secretion with a period of 10-11 min (P less than 0.0001). In addition, somatostatin was secreted from the in vitro pancreas in pulses in phase with insulin (cross-correlation P less than 0.0001). These data are in accord with the theory that the pancreas has an internal pacemaker which controls insulin secretion, and that the amplitude of the oscillations is modulated by vagal control. The pacing of the islets may be coordinated by a neural network, whereas coincident pulsatile somatostatin release may temporarily suppress islet secretion and help to synchronize hormonal oscillations.